Horizontal gene transfer: an insight into antimicrobial resistance - Tanveer, Mahbubul Hoque; Rafa, Atihar Arzu; Sharma, Arnob; Islam, Tashfia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.